Optimasi formulasi dan uji fisik sediaan toner dari minyak atsiri lavender (Lavandula angustifolia l.) sebagai anti jerawat - Ahmad , Rofi’uddin; Ainiyah , Nur (Journal of Pharmaceutical and Sciences, 2025)
Lavender is a light lavender-colored flower, has a distinctive and delicate smell, and has anti-inflammatory, antiseptic, antibacterial, antifungal, antidepressant, and can reduce acne. The purpose of this study is to make a toner preparation formulation from lavender essential oil as an anti-acne with variations in glycerin and propylene glycol concentrations so that an optimal formula is produced. The method used in this study is Simplex Lattice Design. The physical tests of toner preparations carried out include organoleptic, homogeneity, pH, dry time, and displaced volume. The response from the physical evaluation was processed to obtain the optimal formula. The results of the physical test of the optimum preparation were then analyzed using the One Sample T-Test with the SPSS application. Formula optimization yielded a concentration of 10% glycerin and 7% propylenglycol. The optimal preparation of lavender toner is clear white with a distinctive lavender smell and liquid form, a homogeneous preparation, a pH value of 6.17, a drying time of 1.12 minutes, and a transferred volume of 98 ml so that the optimal preparation of lavender toner meets the requirements of a good toner. The results of the One Sample T-Test analysis showed no difference.